Monetary policy shocks in the euro area and global liquidity spillovers - Jo\~ao Sousa; Andrea Zaghini (European Central Bank (ECB), 2004)
This paper analyses the international transmission of monetary shocks with a special focus on the effects of foreign money ("global liquidity") on the euro area. We estimate structural VAR models for the euro area and the global economy including a global liquidity aggregate. The impulse responses obtained show that a positive shock to extra-euro area liquidity leads to permanent increases in the euro area M3 aggregate and the price level, a temporary rise in real output and a temporary appreciation of the real effective exchange rate of the euro. Moreover, we find that innovations in global liquidity play an important role in explaining price and output fluctuations in the euro area and in the global economy.
Keywords: E52; F01; 330; International spillovers; monetary policy; Structural VAR